Penerapan Sistem Informasi Akuntansi Berbasis Accurate Terhadap Penyusuanan Laporan Keuangan - Fuzi Rifka Sallam; Nilda Tartilla (LPPM IBI Kesatuan, 2022)
Small and Medium Enterprises have increased, but few MSMEs have implemented accounting systems. Accounting Information System is increasingly increasing in the field of accounting certainly makes it easier for companies to produce financial reports in addition to facilitate the recording and can find out the company's financial condition. Financial statements that contain financial statements, company performance, and changes in financial position, inventory, and profits obtained which can help the company's internal parties in making decisions. Almuhajir Tugujaya Convection is a manufacturing company where the company produces clothing and shoes. The recording applied by the Almuhajir Tugujaya Convection is still done manually with the excel program, and only records cash receipts and disbursements, so that the owner does not know for sure the inventory, profits and losses obtained. Manual recording results in recording errors and the risk of data loss. The method used by the author in this study is qualitative with the type of case study. The data obtained is processed and then implemented into Accurate 4.0 Software. From this study, it can be concluded that the application of Accurate Software in the Almuhajir Tugujaya Convection can produce Financial Statements in accordance with current standards, and company profits or losses. Research results, after using Accurate at Almuhajir Tugujaya Convection, computerized sales and purchases transactions make it easy to input transactions. Making different formulas for each production can make it easier to find out the inventory stock, and know the production costs of each product. The resulting financial statements are precise and accurate in accordance with current standards, and can help internal parties know the company's condition in making decisions. The risk of data loss and errors in recording can be prevented. Keywords:Financial Statement, Manufacture, Software Accurate Enterprise 4.0